MENJADI IBU TERBAIK: KONTESTASI WEST & ORIENT MOTHER DALAM TERJEMAHAN LITTLE FIRES EVERYWHERE - Kusumaningrum, Ayu Fitri (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
Orientalism is synonymous with the Western male view of Eastern men and women. The discourse of Orientalism is a masculine discourse that rarely portrays women, especially mothers, as subjects of analysis. The problem of this research lies in the Orientalist discourse in the Indonesian version of the novel